KELAYAKAN MEDIA PEMBELAJARAN MACROMEDIA FLASH 8 MULTIPLE INTELLIGENCES KELAS IV SD - Jois Syahadati Masruriyah; Galih Istiningsih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article is focused on the lack of students' mathematical communication in learning mathematics, especially in the length of the material unit. In addition, this article discusses a study about the feasibility of a learning media, namely